Analisis Faktor Kesehatan Kondisi Kerja Dan Kompensasi Yang Diterima Karyawan Dalam Usaha Peningkatan Produktivitas Perusahaan Pada CV. Pusat Jaya Pati - Henny Henny (Jurnal Riset Ekonomi dan Akuntansi, 2023)
High quality human resources really help achieve company goals. Employees have a say not only in the type of organization that will ultimately emerge from it, but also in the way it will mature into a stronger entity. It would be beneficial for a company to have knowledgeable and reliable personnel. The aim of this research is to understand well how to analyze human resource performance at CV. Jaya Pati Center which reflects employee work productivity. This research uses data from 35 (thirty five) CV workers. Jaya Pati Center using a systematic random sampling method and a technical questionnaire. An in-depth regressive analysis strategy was used in this research investigation. The results of this research show that the work environment and employee compensation have a positive and statistically significant influence on worker productivity. Apart from that, the work environment has a positive and statistically significant effect on employee productivity, while remuneration has a positive effect on worker productivity, although this effect is not statistically significant. It is strongly recommended that companies provide their workers with adequate working conditions and pay them fair wages for the tasks they perform.